BLOCKCHAIN AND SMART CONTRACT-BASED DESIGN AND IMPLEMENTATION OF AUTOMATED AGRICULTURAL INSURANCE CLAIMS - Yu, Wang; Muhammad Asraf, Abdullah; Josephine Yau, Tan Hwang (Scibulcom Ltd., 2025)
Smallholder farmers in developing regions face substantial climate-related risks, yet insurance uptake remains very low due to high costs, slow claim settlements, and lack of trust in insurers. This paper proposes a blockchain-based agricultural insurance platform that automates claim processing through smart contracts and trusted data oracles. The system is designed to deliver rapid, fair payouts triggered by real-time weather events, greatly reducing administrative overhead. We implemented and evaluated the platform against traditional manual insurance and a baseline blockchain solution. The results show an order-of-magnitude speedup in claim settlement (days to hours) and about 30–50% lower on-chain processing costs, while maintaining scalability and robust security. The solution’s transparency and efficiency are expected to increase smallholder farmers’ trust and participation in crop insurance programs. This work demonstrates that a carefully engineered blockchain smart contract system can overcome key barriers in agricultural insurance, offering a viable path to protect vulnerable farming communities against climate risks.